Power equations in endurance sports - van Ingen Schenau, G. J.; Cavanagh, P. R. (Journal of Biomechanics, 1990)
This paper attempts to clarify the formulation of power equations applicable to a variety of endurance activities. An accurate accounting of the relationship between the metabolic power input and the mechanical power output is still elusive, due to such issues as storage and recovery of strain energy and the differing energy costs of concentric and eccentric muscle actions. Nevertheless, an instantaneous approach is presented which is based upon the application of conventional Newtonian mechanics to a rigid segment model of the body, and does not contain assumptions regarding the exact nature of segmental interactions—such as energy transfer, etc. The application of the equation to running, cycling, speed skating, swimming and rowing is discussed and definitions of power, efficiency, and economy are presented.